The differences of gross motor development level among Taekwondo athletes - Abdullah, Borhannudin; Tan, Kien Kok (IDOSI Publications, 2014)
This study was conducted to identify the level of gross motor development Taekwondo athletes in the early stages of schooling. Methods: A total of 120 participants (M = 60, F = 60) participated in this study. Ulrich Gross Motor Development Test (2000) was conducted to determine the level of gross motor development Taekwondo athletes in terms of locomotor skills and object control skills. Scores obtained by Taekwondo athletes have been transcribed for locomotor standard score and score object control standard Gross Motor Development Quotient (GMDQ). ANOVA statistical analysis is used to analyze the findings in comparing scores mean Taekwondo athletes based on age groups. In addition, different levels of locomotor skills age equivalents and age equivalents in the object control skills among Taekwondo athletes aged 8 years to 10 years were also studied. Findings: Results showed significant differences in the level of locomotor age equivalents (F 2,117; 14 162; p <0.000), age equivalent level object control skills (F 2,117; 31 675; p <0.000) and the level of gross motor development (F 2,117 : 15 423: p <0.000) between the age group athletes Taekwondo. Results and Discussion: The study shows that there is deviation in the development of gross motor skills among Taekwondo athletes in the early stages of schooling.